Effect Of Different Muscles On The Quality And Color Stability During Aging Of Hot-Boned Sheep Meat - Kapase, Gangadhar; Kulkarni, Shrikant; M, Kiran; M Govindaiah, Prasad; S M, Kartikesh; G P, Kalmath (Journal of Meat Science, 2024)
This study investigated the impact of conditioning on muscle-specific meat quality in various muscle types, including Vastus lateralis (VL), Gluteo biceps femoris (GBF), Gluteomedius (GM), Longissimus dorsi et lumborum (LL), Psoas major (PM), and Semitendinosus (ST) in sheep. Meat qualityparameters such as water holding capacity (WHC), thiobarbituric acid reactive substance (TBARS), drip loss, and color stability (myoglobin [Mb], met-myoglobin [met-Mb], instrumental color [L*, a* and b*]) were assessed under refrigeration conditions (4±1 º C) on the 0th, 5th, 10th, and 15th day post-mortem. The findings of this study indicated a significant decrease (P
Keywords: Meat quality; Ageing; myoglobin; water holding caapcity; color stability; Colorstability